Currículo e arquitetura escolar: concepções de professoras e equipe gestora do Colégio Nossa Senhora das Neves-Natal-RN - Oliveira, Karina de (2012)
The present study aims to investigate the conceptions of teachers and management team of the Colégio Nossa Senhora das Neves - Natal / RN about curriculum, school architecture and possible relationships established between these components. To develop the study, we rely on the theoretical contributions of Viñao Frago (2001), Escolano (2001); Benconstta (2005), among others, about the architecture school, and with regard to curriculum, ancoramo us in theoretical reflections Silva (2000, 2006, 2008). We assume that the school place is a social construct and as such, reflects the interests of certain groups, to organize, establish ways to condition their unctions and uses. In this space, people's lives is planned, both those who work there, as those who study there. Thus, the architecture school promotes, through representations, signs, symbols and shapes, certain charges that impact the ways of being and acting subjects by establishing appropriation and expropriation of rights and legitimate forms of inclusion and exclusion. Thus, it is an expression of power. A power that is expressed in the form of lead the way people should behave in a certain space. Clarity on these aspects of the architecture school is important, since in the same way that the opinion of several experts is important to discuss the adequacy of school architecture (environmentalists, architects, engineers, planners), the / the teacher / and the / as managers / must also meet the educational nature of the architecture school, so as to present its share of contribution in order to make the post-school conducive to learning multiple. From this perspective, we analyze the concepts of four teachers and eight individuals who are part of the management team of the CNSN, whose views were seized through participant observation, semi-structured interviews and documentary analysis. The construction of the data indicated levels of conceptual curriculum varied, ranging from those rooted in traditional theories of curriculum as those regarding the curriculum tied to discursive and contextual aspects. The conceptions of architecture school, predominantly focused on the aspects of the architecture school materials and most established subject, differently, relations between curriculum and school architecture